Pengaruh Penerapan Metode Discovery Learning Terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas VIII SMP Swasta HKBP Sidorame Medan - Siregar, Mallasak; Saragih, Elza L.L.; Simanjuntak, Harlen (Lembaga Riset dan Inovasi Almatani, 2024)
This research aims to determine the effect of using the Discovery Learning Method on the ability to write explanatory texts for class VIII students at HKBP Sidorame Middle School, Medan. This research uses a quantitative experimental research method with a one group pretest design. The population in the study was all 30 class VIII students. The data analysis techniques used were normality test, homogeneity test and hypothesis test. After conducting research for pretest and posttest experiments using the Discovery Learning Method, the average score for the control class was 60.93 and the experimental class average was 80.8. The pre-test and post-test data prerequisite test results stated that the sample had a normal and homogeneous distribution. From the results of research hypothesis testing, a